Self-presentation dan kesadaran privacy micro-influencer di instagram (Jurnal Studi Komunikasi, 2020)
Instagram is a platform that can be used to express online self-presentation by uploading contents. Micro-influencers also perform the self-presentation to maintain their existence on social media. However, we cannot be sure if everything shown in social media are actual representation of the influencer’s real lives. Social media users also threatened by privacy issue. This research attempted to find out self-presentation strategies applied by micro-influencers on Instagram, as well as the differences between front stage and back stage by using dramaturgy theory by Erving Goffman. This research also studied the privacy awareness of micro-influencers on Instagram. The results of this study indicated that micro-influencers only display positive content on Instagram. The study also revealed that there are differences between front stage and back stage shown by micro-influencers on Instagram. Then, this study also found that both influencers are concerned of their privacy on Instagram. Consequently, they use privacy features offered by Instagram.